Avascular necrosis with non-union of the scaphoid managed with a dorsal pedicled vascularised bone graft of the distal radius: a case report - Rao Venkata Mahipathy, Surya Rao; Durairaj, Alagar Raja; Sundaramurthy, Narayanamurthy; Jayachandiran, Anand P.; Rajendran, Suresh (International Surgery Journal, 2021)
Avascular necrosis (AVN) of the scaphoid is common following proximal pole fractures due to an arduous retrograde arterial vascular supply and it is a challenge to the hand surgeon. The treatment for scaphoid non-union with avascular necrosis is vascularized or non-vascularized bone grafts. Non vascularised bone grafts (NVBGs) can be categorized as autograft or allograft and cancellous or cortical bone grafts. Vascularised bone grafts promote biological healing and revascularizes ischaemic bone and they are free or pedicled grafts. Pedicled vascularised bone grafts maintain the vascular supply of the donor bone graft and this leads to better bone remodelling, less osteopenia, faster incorporation and better maintenance of bone mass compared to the non-vascularised graft with good clinical and radiological outcomes. In this paper, we have treated avascular necrosis of scaphoid with a pedicled vascularised bone graft based on the 1, 2 intercompartmental supraretinacular artery (1, 2-ICSRA) that resulted in a favourable outcome.